HISTOMORPHOLOGICAL VARIATIONS OF THE LIVER IN CHRONIC ALCOHOL EXPOSURE: AN ANATOMICAL STUDY (Asian Journal of Medical Research and Health Sciences, 2026)
Background: The consumption of alcohol over extended periods becomes one of the primary causes which leads to both structural and functional damage of the liver. The investigation of histomorphological changes enables researchers to measure the degree of alcohol-related liver damage in their study subjects. Objective: Researchers conducted the study to examine and contrast the histomorphological changes present in liver tissue between people who consume alcohol chronically and those who do not. Methods: A comparative anatomical study was conducted on 120 liver specimens, divided equally into Chronic Alcohol Exposure (n = 60) and Control (n = 60) groups. The study measured three histomorphological parameters which included hepatocyte size (µm) and central vein diameter (µm) and fibrosis score. The researchers first computed descriptive statistics before they used one-way ANOVA (Welch’s and Fisher’s tests) to identify intergroup differences. The researchers evaluated normality assumptions through the analysis of Q–Q plots which displayed standardized residuals. Results: The chronic alcohol exposure group demonstrated significantly increased mean hepatocyte size (23.99 ± 1.698 µm), central vein diameter (120.57 ± 10.364 µm), and fibrosis score (3.52 ± 0.381) compared to controls (17.77 ± 1.363 µm; 90.74 ± 7.969 µm; 1.19 ± 0.313 respectively). One-way ANOVA revealed highly significant differences across all parameters (p < .001). The distribution analysis confirmed that researchers could proceed with parametric testing because the data met normality requirements. Conclusion: Chronic alcohol exposure causes extensive liver cell growth and blood vessel widening and advancing liver tissue scarring which results in complete destruction of liver structure. The research demonstrates strong evidence through both morphological observations and statistical analysis which shows that alcohol causes liver damage.